Gender Mainstreaming through Guarantees of Legal Protection and Access to Justice for Women and Children in Religious Court - Andi Akram; Agus Digdo Nugroho; Reihan Putri; Johanes Johanes (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Barriers to realizing accessibility for women and children in religious courts are still quite significant. Even after five years have passed since Supreme Court Regulation Number 3 of 2017 on Guidelines for Trying Women’s Cases in Conflict with the Law was published. The initial suspicion is that this is still an unresolved problem because law enforcement’s sensitivity to the needs of women and children has yet to be developed. Gender mainstreaming is then encouraged to overcome this. The problem that is the focus of discussion in this research is how to increase the accessibility of justice for women and children in religious courts. The aim is to elaborate and analyze the problem of how to increase the accessibility of justice for women and children in religious courts. The research method used is normative juridical, the research specification is descriptive analysis, and the data collection technique is library research. The research results show that most of the existing obstacles in access to justice and law for women and children after divorce still exist and still need to be resolved. The Supreme Court, as the supervisor of religious courts, has issued several regulations to overcome this problem. In fact, after several of these regulations were issued, difficulties with access to justice continued to occur, primarily related to the implementation of decisions/ executions. Gender mainstreaming by judges and religious court officials is needed to narrow the gap in access to justice and law for women and children after divorce. The urgency is because women and children are vulnerable parties, have limitations, and have extensive obstacles in accessing justice in court. Hence, they require support for convenience, priority access, simplification of business processes, and additional authority for judges in their positions (e.g., officio) when handling cases of women and children.